A deadly walk in Devon - George, Nicholas (Novelist) (George, Nicholas (Novelist). Walk through England mystery, 2024)
After a long career as a detective in San Diego, Rick "Chase" Chasen has traded in his badge for a change of scenery in the coastal comforts of Devon, England, until a local murder takes him on a deadly detour... Still grieving the death of his long-time partner, Chase reunites with his dear friend and fellow Anglophile Billie Mondreau for a seacoast holiday of historic sightseeing. Assigned a pair of guides from the tour company Wanderers, Chase and Billie join seven other like-minded Americans looking forward to an English getaway. All except for Ronald Gretz. The wealthy entrepreneur behind the international Golden Sunset nursing home chain doesn't like anything about walking, touring, or England. Coarse and opinionated, Gretz's complaints get on the nerves of his fellow Wanderers--and his long-suffering trophy wife. But Gretz's gripes are tied to his own nerves being frayed. He has been receiving threatening texts and emails signed "An Avenger." Convinced someone means him harm, Gretz asks Chase to watch his back. Soon, Gretz falls afoul of several "accidents," leading to more friction with the other walkers. Until one final "accident" results in Gretz dead at the bottom of a cliff. Chase, whose investigative instincts remain sharp, knows Gretz's death was no accident. While helping the police investigate, he discovers that members of the tour group not only disliked the victim but had legitimate motives for wanting him dead. Now, he just has to uncover who among them is willing to kill... --